Ejercicios pliométricos en la fuerza explosiva del tren inferior de los deportistas de federación deportiva de Tungurahua disciplina boxeo. - Simbaña Saqui, Ángel Patricio (2022)
This study aims to determine the influence of plyometric exercises in the improvement of explosive strength in boxers of the pre-juvenile and juvenile categories from the Federación Deportiva de Tungurahua (FDT). A quasi-experimental study was developed with two working groups, an experimental one made up of 10 individuals in which a training program was applied for eight weeks based on plyometric exercises, as well as a control group was implemented with the same sample of participants in which a training program based on a traditional methodology. The Squat Jump (SJ) of the Bosco test was applied before the implementation of the program to evaluate the explosive strength of the athletes' lower body. Between the two groups, there were no significant differences, and that in both cases the jumping values were limited. Similarly, the SJ test was applied at the end of the training program, the results obtained in the post-test showed that the participants improved their jumping capacity with respect to the pre-test. Significant differences were observed (p-value < 0.05) using the Wilcoxon signed-rank test for related samples taking into account the higher jump values in the final test with an average increase of 36.03%. On the other hand, the boxers in the control group did not show significant differences, so the training program based on plyometric exercises did contribute to the development of explosive lower body strength in the DFT boxers.